Microsatellite polymorphism in Escherichia coli - a tool to study genetic diversity. - Kua, Guo Wei. (2010)
Correct identification of bacteria is important in the healthcare and commercial sector. Traditionally, strain typing has been done by serology, which is impractical. Many new methods have been developed based on DNA fingerprinting - the most promising being multi-locus variable number tandem repeats analysis (MLVA). As gel electrophoresis is usually used for detection, rapidity is still a problem. In this study, we have adopted MLVA with only selected microsatellites from Escherichia coli. With the 9 selected regions, we could distinguish 10 out of 11 strains. To improve the rapidity, mass spectrometry (MS) was used to analyze one of the regions. Purification of samples was done with ultrafiltration and magnetic bead capture. However, we did not manage to get any significant result from the MS spectrum. Thus, further research is to be done to improve detection by MS and to make microsatellite profiling a routine for identification and characterization of pathogens.